2021
DOI: 10.1590/0034-761220200427
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Africa: a comparative analysis of early policy responses

Abstract: The COVID-19 pandemic has caused turmoil around the world. In Africa, some similarities and differences could be observed in the nature of the outbreak and the policy responses across the continent. This article discusses the policy responses and reflects on their effectiveness as a containment strategy. We speculate on why these strategies seem to work or not, and the lessons therein. The analysis also examines the setting up of crisis teams and whether they indicate lack of trust in the existing public admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The COVID-19 pandemic has caused great turmoil throughout the world. Although it is epidemiological in nature, its impact has extended beyond the health domain (Sotola, Pillay, & Gebreselassie, 2021). To prevent the spread of the virus, as a result of the thousands of confirmed cases worldwide, national and international health authorities have adopted a variety of strategies (Peci, Avellaneda, & Suzuki, 2021) and recommended the implementation of social distancing policies to contain the spread of the virus that causes the disease (Cunha, Domingos, Rocha, & Torres, 2021; Tabari, Amini, Moghadami, & Moosavi, 2020; World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused great turmoil throughout the world. Although it is epidemiological in nature, its impact has extended beyond the health domain (Sotola, Pillay, & Gebreselassie, 2021). To prevent the spread of the virus, as a result of the thousands of confirmed cases worldwide, national and international health authorities have adopted a variety of strategies (Peci, Avellaneda, & Suzuki, 2021) and recommended the implementation of social distancing policies to contain the spread of the virus that causes the disease (Cunha, Domingos, Rocha, & Torres, 2021; Tabari, Amini, Moghadami, & Moosavi, 2020; World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, this study focused only on upper-middle and high-income countries. Another study focused on comparing early COVID-19 policy responses in select countries within Africa in the context of their health systems [ 12 ]. The study found that early implementation of policy responses is important for pandemic management and that past experience with epidemics may be helpful with the COVID-19 response.…”
Section: Introductionmentioning
confidence: 99%
“…LEE;NA, 2020;SCHOMAKER;BAUER, 2020;SOTOLA;PILLAY;GEBRESELASSIE, 2021;. Neste aspecto, no que tange ao Brasil, destaca-se a dificuldade estrutural na preparação, prevenção e mitigação de desastres, o que foi acentuado na pandemia devido à descoordenação das ações e conflitos com governos subnacionais, aumentando as tensões e discordâncias acerca de quais seriam as ações mais adequadas (RODRIGUES; CARPES; RAFFAGNATO, 2020).Além disso, é importante a inclusão da população no processo de tomada de decisão o que, além de facilitar o planejamento e a condução das políticas, aumenta os níveis de confiança e favorece a contenção da pandemia, mesmo diante de decisões inicialmente incorretas (ABDULLAH; KIM, 2020; ALI; AHMED;ANTWI-BOASIAKO et al, 2021;CEPIKU;GIORDANO;MENEGUZZO, 2021;.…”
unclassified